OPERATIONAL ANALYSIS OF RAMPS ON EXISTING FREEWAY - Thamir Ibraheem, Asma (Iraqi Journal of Civil Engineering, 2008)
ABSTRACTAn operational analysis is an analytic evaluation of operation on an existing freeway ramps. In this case, all traffic and roadway conditions must be specified. The output of operational analysis is an estimate of the level of service for the ramp in question and of the approximate speed and density at which the traffic stream operations.A ramp is length of roadway providing an exclusive connection between two highway facilities. On freeways, all entering and exiting maneuvers take place on ramps those are designed to facilitate smooth merging of on-ramp vehicles into the freeway traffic stream and smooth diverging of off-ramp vehicles from the freeway traffic stream onto the ramp.The aim of this paper is the operational analysis of ramps on existing 6-lane freeway. This analysis involves the consideration of known freeway of Mohammed Al-Kasim freeway in Baghdad city. Given known geometric roadway conditions and projected traffic conditions, the operational analysis yields an estimate of the level of service and of the speed and density of the traffic stream. This paper has described the procedure for determining the level of service on Mohammed Al-Kasim freeway ramp sections as presented in the Highway Capacity Manual (HCM, 2000). Levels of service are determined for all ramps of the freeway using )HCS2000( software. Level of service of all ramps are similar at AM and PM peak hour periods, because the data was collected under ordinary traffic conditions.